Poetry and Philosophy, or the World as Possibility and Representation - Benéitez Andrés, Rosa (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Poetry and Philosophy are ways of thinking through language. Their links have been marked by affinities, disagreements and even by certain relationships of disciplinary domination. Within this framework of understanding it is evident that the activity of one and the other has not always been complementary. Therefore, situating ourselves only within a common field of work, that is, when poetry and philosophy establish a declared complicity, this article intends to analyse one of the objectives shared by both, which has also been pointed out, within our tradition, by both poets and philosophers. Specifically, we intend to trace here some of the aesthetic reflections that have understood poetry and philosophy as a critique of the existing and an opening to new possibilities of interpretation, representation and action on the real.
Keywords: Poetry; Philosophy; Literary Aesthetics; Possibility; Contingency; Artistic Usenessless